THE EFFECT OF GREEN RECRUITMENT, GREEN TRAINING ON EMPLOYEE PERFORMANCE IN PT TRU USING ORGANIZATION CITIZENSHIP FOR ENVIRONMENT AS MEDIATION VARIABLE - Sinaga , Siska Agustina; Nawangsari , Lenny C. (Dinasti International Journal of Management Science, 2019)
This study aims to analyze the effect of green recruitment, green training, and OCBE on employee performance. This type of research is carried out quantitatively and for the research method used is the associative explanatory level method. The object of this research is PT TRU. The sampling method used was a probability sampling with a sampling technique using simple random sampling with a total sample of 100 people. Data analysis was performed using Structural Equation Modeling (SEM) with soft ware Partial Least Square (smart – PLS). The results obtained in this study: 1) Green recruitment, green training, and Organization Citizenship for Behavior (OCBE) have positive and significant effect on employee performance, 2) Green recruitment and green training have a positive and significant effect on employee performance through Organization Citizenship for Behavior ( OCBE).